Implementing an evidence-based structured education and management program in an inpatient adult oncology setting to improve patients' pain control. Issue 4 (31st December 2022) - Tien, Jeraine J.N.; Tan, Hui Ching; Chua, Chue Teng; Lee, Yee Mei; Tho, Poh Chi
ABSTRACT: Background and aims: Cancer-related pain is prevalent across the cancer trajectory, and is probably one of the most feared of all cancer symptoms for patients and their families. Although there were guidelines and framework regarding the management of cancer pain, pain control among patients remain suboptimal. This best practice implementation project aimed to improve patients' perception on cancer pain management and pain control through implementing structured patient and family education and patient information leaflet (PIL) on managing cancer pain. Methods: The current implementation project conducted in an adult oncology inpatient unit utilized the JBI Practical Application of Clinical Evidence System and Getting Research into Practice module for promoting evidence-based health care. Results: A comparison between the preimplementation and postimplementation findings showed significant improvements for both audit criteria outcomes. The percentage of patients receiving verbal education rose from 0 to 69%, whereas the percentage of patients receiving PIL increased 0–100%. Patient compliance to analgesic regime increased from 0 to 100%. There was a significant improvement in patients' pain levels ( P  < 0.001), with majority rate having none-mild pain post intervention. Conclusion: A structured educational program on cancer-related pain improved patients' knowledge on cancer-related pain management and pain control. Despite the remarkable increase in the compliance rate, further interventions may still be required to achieve 100% compliance. Continuous audits will be held to guide follow-up interventions to ensure compliance and sustention of the project.